Phospholipase C activation by ethanol in rat hepatocytes is unaffected by chronic ethanol feeding. - Hoek, J B (1990)
The activation of phosphoinositide-specific phospholipase C by ethanol was compared in hepatocytes isolated from ethanol-fed rats and from pair-fed control animals. Ethanol (100-300 mM) caused a dose-dependent transient increase in cytosolic free Ca2+ levels in indo-1-loaded hepatocytes from both groups of animals. The rate of Ca2+ increase was similar in hepatocytes from control and ethanol-fed rats, but the decay of the Ca2+ increase was somewhat slower in the latter preparation. The ethanol-induced Ca2+ increase caused activation of glycogen phosphorylase, with 50% response at 50 mM-ethanol and a maximal response at 150-200 mM-ethanol, not significantly different in hepatocytes from control and ethanol-fed animals. Ins(1,4,5)P3 formation in response to ethanol (300 mM) or vasopressin (2 nM or 40 nM) was also similar in the two preparations. It is concluded that long-term ethanol feeding does not lead to an adaptive response with respect to the ethanol-induced phospholipase C activation in rat hepatocytes. The ability of ethanol in vitro to decrease membrane molecular order in liver plasma membranes from ethanol-fed and control rats was measured by e.s.r. Membranes from ethanol-fed animals had a significantly lower baseline order parameter compared with control preparations (0.313 and 0.327 respectively), indicative of decreased membrane molecular order. Addition of 100 mM-ethanol significantly decreased the order parameter in control preparations by 2.1%, but had no effect on the order parameter of plasma membranes from ethanol-fed rats, indicating that the plasma membranes had developed tolerance to ethanol, similar to other membranes in the liver. Thus the membrane structural changes associated with this membrane tolerance do not modify the ethanol-induced activation of phospholipase C. The transient activation of phospholipase C by ethanol in hepatocytes may play a role in maintaining an adaptive phenotype in rat liver.